2015
DOI: 10.4238/2015.april.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the Cyclemys dentata and phylogenetic analysis of the major family Geoemydidae

Abstract: ABSTRACT. In the present study, the complete mitochondrial (mt) genome of Cyclemys dentata was determined using PCR reactions. The structural organization and gene order of C. dentata were equivalent to those of most other vertebrates. The mt genome was 16,489 bp in length, has rich A+T content, consisting of 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and a control region (D-loop). All protein-coding genes started with ATG, many genes have complete stop codons, except ND2, COX3, ND3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Currently, 31 mitogenomes of species comprising seven Geoemydidae genera ( Mauremys , Cuora , Heosemys , Sacalia , Notochelys , Cyclemys , and Batagur ) are available in GenBank. Among them, only four mitogenomes (, , , and ) of four species ( Batagur trivittata , Cuora mouhotii , Cuora trifasciata , and Cyclemys dentata ) are published (Feng, Yang, Zhang, & Zhao, ; Huang et al, ; Li, Zhang, Zhao, Shi, & Zhu, ; Zhang, Nie, Cao, & Zhan, ). However, no complete mitogenome of any species of Pangshura is available.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 31 mitogenomes of species comprising seven Geoemydidae genera ( Mauremys , Cuora , Heosemys , Sacalia , Notochelys , Cyclemys , and Batagur ) are available in GenBank. Among them, only four mitogenomes (, , , and ) of four species ( Batagur trivittata , Cuora mouhotii , Cuora trifasciata , and Cyclemys dentata ) are published (Feng, Yang, Zhang, & Zhao, ; Huang et al, ; Li, Zhang, Zhao, Shi, & Zhu, ; Zhang, Nie, Cao, & Zhan, ). However, no complete mitogenome of any species of Pangshura is available.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) revealed that the open reading frame begins with 'ATG' (Methionine) and terminates with 'TAA' was similar to other reported Trionychidae species in database, except Pelodiscus sinensis from Republic of Korea (AY962573.1) reported 'ATT' start codon for Cyt b [26] . The AT rich (60%) nucleotide composition of Cyt b gene in current study reflects the characteristic vertebrate mitogenome composition [27] . 'TGA' (or UGA) believed to be a universal termination codon for nuclear genes appeared in the current Cyt b sequence stretch but, here it codes for Tryptophan as in all vertebrate mtDNA [28] .…”
Section: Resultsmentioning
confidence: 58%
“…3 . The overall nucleotide composition consist 33–34% (A), 30–32% (T), 11–12% (G) and 21–22% (C), highlighting AT rich vertebrate mtDNA composition [27] . D-loop sequences (∼1000 bp) analyzed in MEGA v6.06 [21] for intraspecific variations revealed 189 variable sites, 51 parsimony informative sites and only 89 conserved sites.…”
Section: Resultsmentioning
confidence: 98%
“…Similar results have also been reported in several turtles, such as Pangshura spps. (Kundu et al, 2019;2020), Cyclemys dentata (Huang et al, 2015), Pyxidea mouhotii (Zhang et al, 2008b), Cuora trifasciata (Li et al, 2015), and B. trivittata (Feng et al, 2017).…”
Section: Mitogenome Structure and Organizationmentioning
confidence: 99%